Perancangan Pengalaman Pengguna pada Aplikasi Antrean Rumah Sakit menggunakan Metode Human-Centered Design (Studi Kasus: RSUD 45 Kuningan) - Hummam Aly Baziyad; Herman Tolle; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The electronic queueing application of Regional General Hospital 45 Kuningan (RSUD 45 Kuningan) is an application designed for the public as a form of information disclosure and facilitates access to hospital services. This application is made based on the needs of RSUD 45 Kuningan and the extension of cooperation agreement with the Social Security Administration Agency (BPJS) for 2021. This research aims to create user experience design in order for the application to deliver good results for its users in terms of usability and user experience. The method used to perform the design is Human-Centered Design (HCD) which consists of several stages such as user context analysis, user requirements analysis, creating design solutions, and evaluating design solutions. Evaluating design solutions was carried out by conducting usability testing and filling User Experience Questionnaire (UEQ) to 10 respondents and obtained a score of 87.75% in the effectiveness aspect, 0.176 goals/second in the efficiency aspect, and 77.75 with grade B in the user satisfaction aspect. UEQ results on attractiveness, perspicuity, and dependability aspects achieved excellent category. Efficiency and stimulation aspect achieved good category. Lastly, the novelty aspect achieved above-average category. These results show that the design solutions are acceptable with good usability score and positive user experience with above average scores on each aspect.